Squamous cell carcinoma of the ascending colon: two cases. Issue 1 (2nd January 2017) - Abdelqader, Abdelhai; Jabaji, Ramez; Albugeaey, Mohammed; Palese, Caren
ABSTRACT: Squamous cell carcinoma (SCC) of the colon without known primary source is a rare finding that needs aggressive management. We report two cases of SCC of the colon without any clear extra-colonic source despite extensive workup. In our experience, the clinical course and prognosis are largely dependent on the presence of metastatic disease at diagnosis. The main treatment is surgery, with chemotherapy having less defined role.